(untitled) (Prithvi Academic Journal, 2025)
This study investigates the impact of occupational stress on turnover intention among employees of commercial banks in Pokhara Valley, Nepal. Occupational stress, stemming from excessive workloads, role ambiguity, work-life balance, and negative organizational culture, has been recognized as a significant contributor to employee turnover in banking sectors. Using quantitative approach, a causal comparative as well as cross-sectional research design, data was collected through a survey of 136 commercial bank employees. The study applied descriptive and inferential statistical techniques, including correlation and regression analyses, to examine the relationships between key stress factors and turnover intentions. The findings reveal that excessive workload and an unsupportive organizational culture are significant predictors of turnover intention, while role ambiguity and work-life balance had no significant impact in this context. The study concludes that banking institutions should focus on managing workloads and fostering a fair, transparent, and supportive organizational culture to reduce turnover. Addressing these issues may improve employee retention and enhance overall productivity.